(3GdCQHYhf MOjKGs - (3GdMGFQj, GdYdhj GdMSjfj, CHh GdaJM, GHf LYaQ, eMeO Hf eMeOs
(3ChdgG (B:s
(3HSe Gddg (B... (3bGd MOKfG GdTjN GdYGde CHh GdecGQe GHf cJHdI GdYdhj HeTgO ehdGfG CejQ GdeDefjf Ydj Hf CHj WGdH (B.. (3aj LeGOi GdChd SfI KdGKI hNeSjf hNeSeGFI bGd MOKfG CHh YHO Gddg bGd MOKfG ENHGQG hELGRI bGd MOKfG (B...s
(3BNQgG (B:s
... (3hYfge Yf YHO Gddg Hf GdMGQK Yf Ydj Ydjg GdSdGe bGd hLYJ hLYG TOjOG aCJjJ GdfHj Udi Gddg Ydjg hSde aCfGefj aj ecGfg hZWGfj HWQa KhHg hbGe jUdj hjUdj eG TGA Gddg (B...(3aQZJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdMOjK hGdeUWdMs